2017
DOI: 10.1186/s40249-017-0259-5
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged parasite clearance in a Chinese splenectomized patient with falciparum malaria imported from Nigeria

Abstract: BackgroundThe spleen plays a pivotal role in the rapid clearance of parasitized red blood cells in patients with falciparum malaria after artemisinin treatment. Prolonged parasite clearance can be found in patients who have had a splenectomy, or those with hemoglobin abnormalities and/or reduced immunity, which are all distinguishable from artemisinin resistance. This paper reports on a case of prolonged parasite clearance in a Chinese splenectomized patient with falciparum malaria imported from Nigeria.Case p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Also, mature forms of the parasite are more frequently found in the blood, suggesting a lack of sequestration or an inability to clear the parasites in the spleen's absence. 15,[40][41][42][43] In support of the former, a splenectomized patient from Cameroon displayed high parasitemia and the presence of late trophozoites, schizonts, and gametocytes in circulation. RT-PCR analysis on the blood indicated that pRBCs from the patient failed to express members of the var, rifin, and stevor multigene families, and pRBCs failed to bind to host receptors such as CD36 and ICAM-1 in vitro.…”
Section: The Requirement For the Spleen In Protection Against Malariamentioning
confidence: 89%
See 1 more Smart Citation
“…Also, mature forms of the parasite are more frequently found in the blood, suggesting a lack of sequestration or an inability to clear the parasites in the spleen's absence. 15,[40][41][42][43] In support of the former, a splenectomized patient from Cameroon displayed high parasitemia and the presence of late trophozoites, schizonts, and gametocytes in circulation. RT-PCR analysis on the blood indicated that pRBCs from the patient failed to express members of the var, rifin, and stevor multigene families, and pRBCs failed to bind to host receptors such as CD36 and ICAM-1 in vitro.…”
Section: The Requirement For the Spleen In Protection Against Malariamentioning
confidence: 89%
“…During primary infection with P. falciparum , the severity of disease (i.e., increased cerebral malaria), death, and parasite burden are enhanced in splenectomized patients. Also, mature forms of the parasite are more frequently found in the blood, suggesting a lack of sequestration or an inability to clear the parasites in the spleen's absence 15,40–43 . In support of the former, a splenectomized patient from Cameroon displayed high parasitemia and the presence of late trophozoites, schizonts, and gametocytes in circulation.…”
Section: The Requirement For the Spleen In Protection Against Malariamentioning
confidence: 93%
“…It has a coiled-coil-containing (CCC; amino acid from 212-341), broadcomplex, tram track, and bric-a-brac (BTB; amino acid from 350-437) and a C-terminal kelch-repeat propeller (KREP; amino acid from 443-726) which harbours virtually all Pfk13 allelic variants associated with artemisinin resistance (Anderson et al, 2017) (Figure 5). Kelch-13 gene is putatively associated with intraerythrocytic growth and proliferation of both P. falciparum asexual parasites (Bushell et al, 2017;Zhang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Several case reports and small series highlight an increased risk of malaria after splenectomy, however these reports are limited to no more than 33 splenectomized individuals [1, 2, 1214, 22–26]. The current analysis was able to expand the risk analysis from an endemic area where a high number of individuals undergo splenectomy, mostly following trauma or road traffic injuries.…”
Section: Discussionmentioning
confidence: 98%
“…The spleen is vital for immunity to Plasmodium species [1, 711]. Splenectomized patients are more susceptible to severe falciparum malaria and have a greater risk of hospitalization and mortality [1214]. Studies of splenectomized individuals in malaria-endemic regions of Malawi and Papua New Guinea suggest a risk of malaria almost double that of non-splenectomized controls [1, 2].…”
Section: Introductionmentioning
confidence: 99%